2020
DOI: 10.1111/are.14833
|View full text |Cite
|
Sign up to set email alerts
|

Monthly variation of growth, biochemical composition, fatty and amino acids patterns of gilthead sea bream (Sparus aurata) in offshore cage systems under brackish water conditions in the Black Sea

Abstract: The aim of this study was to investigate seasonal variations of growth performance and biochemical composition, fatty and amino acids profiles of cage‐cultured gilthead sea bream (Sparus aurata) in the Black Sea. The research was carried out on a yearly basis in the offshore cage systems of a commercial fish farm located on the coast of Samsun province, Turkey. Fish with an initial average weight of 2.44 ± 0.03 g reached a harvest weight of 474.60 ± 8.64 g with a survival rate of 94.26 ± 0.60% in 14 months. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 92 publications
0
2
1
Order By: Relevance
“…In addition, the biochemical composition values of turbot fillets were lower than previous studies (Manthey-Karl et al, 2016;Hernandez-Urcera et al, 2017). In the remaining three fish species fillets, the CP and CF values were higher than those presented in earlier studies values (Regost et al, 2001;Poontawee et al, 2007;Davidson et al, 2014;Baki et al, 2015;Kaya Öztürk et al, 2019Kaya Öztürk et al, , 2020Tarricone et al, 2022). The biochemical composition of fish fillets did not correlate with the composition of the feed which the fish were fed (r=0.15, p=0.714); (Supplementary file Table S2), because it is not the only parameter that affects the biochemical composition of a fish species.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In addition, the biochemical composition values of turbot fillets were lower than previous studies (Manthey-Karl et al, 2016;Hernandez-Urcera et al, 2017). In the remaining three fish species fillets, the CP and CF values were higher than those presented in earlier studies values (Regost et al, 2001;Poontawee et al, 2007;Davidson et al, 2014;Baki et al, 2015;Kaya Öztürk et al, 2019Kaya Öztürk et al, , 2020Tarricone et al, 2022). The biochemical composition of fish fillets did not correlate with the composition of the feed which the fish were fed (r=0.15, p=0.714); (Supplementary file Table S2), because it is not the only parameter that affects the biochemical composition of a fish species.…”
Section: Discussioncontrasting
confidence: 54%
“…Carcass yields (CY) differ between species ( CY could increase or decrease only depending on the fish species. So much so that while the CY of sea bass and rainbow trout with a fusiform body shape approaches 50% (Baki et al, 2015;Kaya Öztürk et al, 2019;Tarricone et al, 2022), this rate varies between 30% and 50% in large-headed sea bream (Kaya Öztürk et al, 2020), and decreases to 20% in a flat-bodied turbot (Malcorps et al, 2021). a, b: The differences between the means with different letters on the same line within the group are statistically significant (p<0.05).…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that water temperature affects fish metabolism. Optimum temperature range for gilthead sea bream was reported as 20–25 °C (Öztürk et al, 2020). Durmuş (2019) found that the lipid amount, DHA and n‐6/n‐3 ratio of gilthead seabream, which had been captured from the Mediterranean coast, was 1.27%, 19.08%, and 0.09%, respectively.…”
Section: Discussionmentioning
confidence: 99%